Virtual Reality and Its Application in Education - Cvetković, Dragan (IntechOpen, 2021)
Virtual reality is a set of technologies that enables two-way communication, from computer to user and vice versa. In one direction, technologies are used to synthesize visual, auditory, tactile, and sometimes other sensory experiences in order to provide the illusion that practically non-existent things can be seen, heard, touched, or otherwise felt. In the other direction, technologies are used to adequately record human movements, sounds, or other potential input data that computers can process and use. This book contains six chapters that cover topics including definitions and principles of VR, devices, educational design principles for effective use of VR, technology education, and use of VR in technical and natural sciences.